A comparative study of clinical characteristics, work‐up, treatment, and association to malignancy in dermatomyositis between two tertiary skin centers in the USA and Singapore. (27th July 2012) - Yosipovitch, Gil; Tan, Audrey; LoSicco, Katherine; Manabat, Catherine G; Kannagra, Ajith; Carroll, Christie; Chan, Yiong Huak; Ng, Patricia; Jorizzo, Joseph
Abstract Background To date, no study has compared the clinical characteristics, malignancy associations, and treatment of dermatomyositis in predominantly Caucasian vs. Asian populations. Materials and methods This prospective study was conducted to compare clinical characteristics of dermatomyositis, its relationship to malignancy, and treatment between two tertiary medical centers in the USA and Singapore. A total of 19 newly‐diagnosed patients in the USA and 15 patients in Singapore were enrolled. Dermatomyositis or amyopathic dermatomyositis were diagnosed based on clinical assessment, skin and muscle biopsies, and muscle testing. Results Ninety‐five percent of patients in the USA group were of Caucasian descent, while 93% of patients in the Singapore group were of Chinese descent. Both groups were predominantly female. Pruritus was the most common initial symptom reported in both groups, while periungual erythema and Gottron's papules were the most common skin presentations. Heliotrope eruption was more common in the Singapore group, occurring in 80% of patients vs. 32% of patients in the USA group (P = 0.007). Three patients in the Singapore group developed a malignancy, with two of these patients having nasopharyngeal carcinoma. None of the USA patients developed malignancies in a follow‐ up period of 2–5 years. Immunosuppressive steroid sparing therapy with hydroxychloroquine was more frequently used in Singapore, while topical tacrolimus was more frequently used in the USA. Conclusion The clinical presentations of dermatomyositis vary among different ethnic populations. Chinese patients with dermatomyositis have a significant risk for nasopharyngeal carcinoma.